Analisis Potensi Tanah Longsor Menggunakan Metode Geolistrik di Dusun Plalar Kecamatan Banyubiru Kabupaten Semarang - Lutfiana, Hilma; Wahyudi; Hartantyo, Eddy (Universitas Pembangunan Nasional (UPN), 2025)
Landslide in 2019 was the worst incident in Sodong Hamlet and Plalar Hamlet in Kemambang Village. To date, no scientific research has been conducted to assess the landslide potential in this area. Accordingly, this research aims to model subsurface lithological structure in landslide-prone zones -specifically in Plalar Hamlet- using the geoelectrical resistivity geophysical method. Data acquisition was carried out using the Electrical Resistivity Tomography (ERT) technique with a dipole-dipole configuration across six profiles, each extending 160 meters in length. Complementary Vertical Electrical Sounding (VES) surveys employing the Schlumberger array were also conducted at two locations. Interpretation of the data reveals the presence of a slip surface at a depth of approximately 15 meters, with an average slope inclination of 31o. Analysis of rainfall records indicates that landslide occurrences in the region are primarily triggered by high precipitation frequency during the December to February period. The potential runout distance of landslide material is estimate to be around 320 meters, with a projected flow velocity ranging between 1.5 and 2.0 meters per second. Furthermore, the maximum volume of displaceable weathered soil is estimated at approximately 200,000 m3. Keywords: geoelectrical; landslide; lithology